2017
DOI: 10.18632/oncotarget.17159
|View full text |Cite
|
Sign up to set email alerts
|

Identification of eight genetic variants as novel determinants of dyslipidemia in Japanese by exome-wide association studies

Abstract: We have performed exome-wide association studies to identify single nucleotide polymorphisms that influence serum concentrations of triglycerides, high density lipoprotein (HDL)–cholesterol, or low density lipoprotein (LDL)–cholesterol or confer susceptibility to hypertriglyceridemia, hypo–HDL-cholesterolemia, or hyper–LDL-cholesterolemia in Japanese. Exome-wide association studies for serum triglycerides (13,414 subjects), HDL-cholesterol (14,119 subjects), LDL-cholesterol (13,577 subjects), hypertriglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The associations of eight of the nine SNPs [rs7771335 (P=1.00×10 −7 ), rs2071653 (P=1.61×10 −5 ), rs2853969 (P= 6.16×10 −8 ), rs2269704 (P=2.92×10 −7 ), rs2269703 (P=3.67×10 −7 ), rs495089 (P= 0.0 0 01), rs2269702 (P=5.13×10 −7 ) and rs1233399 (P=0.0009)] with hyper-LDL-cholesterolemia were replicated in the present study. Although the association of most SNPs with dyslipidemia identified in our previous study ( 28 ) was replicated, genetic variants associated with hypertriglyceridemia, hypo-HDL-cholesterolemia, or hyper-LDL-cholesterolemia appear to differ, at least in part, between early- and late-onset forms of the diseases.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The associations of eight of the nine SNPs [rs7771335 (P=1.00×10 −7 ), rs2071653 (P=1.61×10 −5 ), rs2853969 (P= 6.16×10 −8 ), rs2269704 (P=2.92×10 −7 ), rs2269703 (P=3.67×10 −7 ), rs495089 (P= 0.0 0 01), rs2269702 (P=5.13×10 −7 ) and rs1233399 (P=0.0009)] with hyper-LDL-cholesterolemia were replicated in the present study. Although the association of most SNPs with dyslipidemia identified in our previous study ( 28 ) was replicated, genetic variants associated with hypertriglyceridemia, hypo-HDL-cholesterolemia, or hyper-LDL-cholesterolemia appear to differ, at least in part, between early- and late-onset forms of the diseases.…”
Section: Discussionmentioning
confidence: 62%
“…Our group has previously reported that two, three and nine SNPs were associated with hypertriglyceridemia (P<1.71×10 −4 ), hypo-HDL-cholesterolemia (P<1.44×10 −4 ), and hyper-LDL-cholesterolemia (P<1.10×10 −4 ), respectively, as determined by multivariable logistic regression analysis with adjustment for age and sex, following an initial EWAS screening of allele frequencies among subjects with early- or late-onset forms of these conditions ( 28 ). The associations of the two SNPs [rs10790162 (P=3.58×10 −24 ) and rs7350481 (P=7.94×10 −23 )] with hypertriglyceridemia were replicated (P<0.05) in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for the difference between these two studies could be that they were conducted in people of different ethnicities and ages. A recent exome-wide association study (EWAS) (Yamada et al 2017) performed in a Japanese population indicated that APOA4 rs5104 located in this gene was associated with the serum TG concentration. A genome-wide association study (GWAS) conducted in Chinese people (Zhou et al 2013) showed that rs651821 presented a strong association with TG levels.…”
Section: Discussionmentioning
confidence: 99%
“…We applied the selection criteria for subjects used in a similar study in a Japanese cohort published in 2017 (Yamada et al, ) to compare our results with theirs. The case and control groups for hypertriglyceridemia, hypo‐HDL‐cholesterolemia, hyper‐LDL‐cholesterolemia, and dyslipidemia were classified based on the classification criteria specified by Yamada et al ().…”
Section: Methodsmentioning
confidence: 99%